The colonisation of Czech travellers and expatriates living in the Czech Republic by colistin-resistant Enterobacteriaceae and whole genome characterisation of E. coli isolates harbouring the mcr-1 genes on a plasmid or chromosome: A cross-sectional study - Krutova, Marcela; Kalova, Alzbeta; Nycova, Elka; Gelbicova, Tereza; Karpiskova, Renata; Smelikova, Eva; Nyc, Otakar; Drevinek, Pavel; Tkadlec, Jan (Travel medicine and infectious disease, 2021)
BACKGROUND: Travellers were recognized as a risk cohort that can be colonized by mcr-1-mediated colistin-resistant Enterobacteriaceae. We aimed to investigate the carriage of mcr-mediated colistin resistance in Enterobacteriaceae in Czech travellers or expatriates residing temporarily in the Czech Republic. METHODS: Between August 2018 and September 2019, the stool samples were cultured in enrichment broth. The enriched cultures were tested for the presence of the mcr-1-8 genes and inoculated onto selective agar with colistin. Colistin-resistant Enterobacteriaceae were tested for the presence of the mcr-1-8 genes; the mcr-positive isolates were characterised by whole genome sequencing. RESULTS: From the 177 stool samples, 15 colistin-resistant Enterobacteriaceae isolates were cultured (7.9%); two of the E. coli isolates carried the mcr-1 gene (1.1%). In the E. coli multilocus sequence type (ST) 156, the mcr-1 gene was located in an ISApl1-mcr-1-orf-ISApl1 (Tn6330) and incorporated into the chromosome; in the E. coli ST23 isolate, the mcr-1 gene was harboured by the plasmid IncX4. Both of the mcr-1 positive E. coli isolates were multidrug-resistant and one isolate was an extended-spectrum β-lactamase producer (blaCTX-M-27). CONCLUSION: Patients with an international travel history should be monitored for the carriage of the mcr-1 gene in order to prevent its dissemination into healthcare settings.
Keywords: kolistin; mikrobiální testy citlivosti; Colistin; Escherichia coli; IncX4; průřezové studie; lidé; Italy; Anti-Bacterial Agents; New Zealand; proteiny z Escherichia coli; bakteriální léková rezistence; Microbial Sensitivity Tests; Chromosomes; Cross-Sectional Studies; plazmidy; Czech Republic; ESBL; Česká republika; Plasmids; ST 23; antibakteriální látky; chromozomy; Drug Resistance, Bacterial; ST 156; Enterobacteriaceae; Escherichia coli Proteins; Faecal carriage; Humans